Development of Methods and Determination of Areas of Application of Textile Materials Treated with a New Fire Retardant Composition - Doschanov, M.; Rafikov, A.; Yuldosheva, O. M. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides information on improving the development of methods for the use of combustible textile materials treated with a new composition.